Diffuse B-cell lymphoma of the testis presenting as epididymo-orchitis - Patrick Davol; Callie Davol (Urology Case Reports)
B-cell lymphoma is the most common type of lymphoma, accounting for 85 percent of all lymphomas in the United States. It is more common in men and older adults, and typically presents with fever, night sweats, fatigue, weight loss, and swollen lymph nodes. Primary testicular lymphoma is rare, representing only 1–2% of non-Hodgkin's lymphomas, and can present a diagnostic challenge with its clinical presentation. We present an unusual presentation of testicular lymphoma in an elderly man, and discuss the challenges in the diagnosis and treatment of this condition.